Dionisian body, Facebook and cultural consumptions: the narratives of the wall (Impetus, 2021)
This article aims to discern the meanings and symbolic contents of consumption produced, exchanged, appropriated and performatized by young people in the social network Facebook from the photographs published by them on this virtual platform. These reflections are the product of an ethnographic study entitled “From the Wall, a look at the speeches projected by the body on Facebook”, which was developed with university students from the city of Villavicencio, Colombia.